Identifying the impact of generalization on maps of erosion dissection at different scales - Hodzinska, Iryna (Reports on Geodesy and Geoinformatics, 2023)
The issue of building thematic maps of erosion dissection, despite its wide demand in various fields of human activity(construction of hydraulic structures, transport and housing construction, agriculture), still has no clear rules and instructions,which causes different perceptions of the obtained mapping results by specialists. The purpose of the study is to experimentallyidentify the change in the index of erosive dissection depending on the scale of the initial data, the size of the cell, the method ofconstructing the thematic map, etc. The methods used in this research are the method of mathematical statistics, GIS mappingand modelling, spatial analysis, and change detection. For each of the selected methods of thematic mapping, we compiled thecartograms that allow the visual tracking of changes in the elements of the erosion network depending on the geometriccharacteristics of the scale and cell size. The dimensions and characteristics with optimal results were substantiated. The mainfeature of erosional dissection mapping of any territory is to detect the negative relief or concave upward forms. The result is avisual perception accompanied by the addition of numerical values. Estimation of erosion dissection by these methods was used inthe construction of a thematic map of the foothill territory with a relatively homogeneous relief pattern. It should be noted that thechange in the morphometric index happens simultaneously with the change in orographic features. Therefore, for areas withdifferent forms of relief, the combination or use of only one of the above methods allows identifying the optimal and most accurateone among them. The use of well-established methods will facilitate the study of foothill plains or mountainous areas and willallow expanding the scope of the use of thematic maps for applied purposes and forecasting.
Keywords: generalization, GIS, mapping, morphometry, surface, relief